Overcoming regulatory barriers to the implementation of AI agents in healthcare - Freyer, Oscar; Jayabalan, Sanddhya; Kather, Jakob Nikolas; Gilbert, Stephen (Nature medicine, 2025)
To facilitate the safe and effective implementation of autonomous artificial intelligence agents in healthcare, regulatory frameworks must evolve beyond static device paradigms to incorporate adaptive oversight and flexible pathways.